Ritme dan Rima serta Amanat Huruf Ba’ dalam Diwan Asy-Syathiri (Kajian Strukturalisme) - Dita Rohmaetul Aeni; Supriadi, Dedi; Nurhasan, Muhammad (Jurusan Pendidikan Bahasa Arab, 2025)
This research analyzes rhythm and rhyme as well as the message of the letter ba' contained in the diwan ash-syathiri by Sheikh Abdullah Bin Umar Ash-syathiri. This diwan contains poems about hikayat of life, morals, and spiritual experiences composed by Imam Ash-syathiri. The purpose of this research is to determine the rhythm and rhyme as well as the message in the letter ba' contained in the diwan Ash-syathiri by Sheikh Abdullah Bin Umar Ash-syathiri. This qualitative research uses the library method for data collection. Data analysis technique used is descriptive analytical method by analyzing the intrinsic elements, such as rhythm, rhyme and message which are presented descriptively. The results of this research indicate that this diwan contains rhythm (arudh) which is characterized by the presence of zihaf and illat. Then rhyme (qawafi) is characterized by the presence of qafiyah sentences, letters, harakat, types, names and varriations (uyub) qafiyah. Then, the message is characterized by the message or information obtained from each piece of verse in Ash-Syathiri's diwan.